El hipérbaton de Góngora y el latín - Bartolomé Pozuelo Calero (E-Spania)
The alteration of the natural word order is an intrinsic feature of Latin poetry, as is also the case in Gongora’s poetry. The question is whether Góngora's word order is the result of the imitation of Latin, or, alternatively, a contrived complication of the word order within the Castilian language itself. This paper outlines the main types of Gongorean hyperbaton and, in each case, documents analogous structures from Latin poetry, while demonstrating that not all of the Latin structures are imitated. This leads to the conclusion that when it comes to Góngora's word order two factors intervene: on the one hand, the conscious desire to reproduce those structures commonly used by the Latin poets, which is understandable within the context of Latin humanism; on the other, the Castilian system, which places certain limits on their use.